2014
DOI: 10.1002/clen.201400141
|View full text |Cite
|
Sign up to set email alerts
|

Combined Ozone and Biological Treatment of Oak Wood Leachate

Abstract: In the present study, we investigated the possibility of treating oak wood leachate with a combined ozone and biological treatment. Wood leachate is characterized by high amounts of organic carbon and is reported as being toxic to aquatic organisms. Ozone was used as a pre‐treatment before using aerobic degradation. The biological treatment was applied for seven days and evaluated using head‐space respirometry. Target pollutant in this investigation was polyphenols in combination with more general parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Field et al (1988) found that 30-50% of the soluble COD from bark water could be acidified into volatile fatty acids (VFAs) and between 7 and 36% could be converted by methanogenesis to methane after 8-9 days of anaerobic digestion. In the case that near complete removal of the remaining DOM was required, post-treatment by combined ozone and biological treatment may be effective at treating woodchip leachate (Zenaitis et al 2002;Svennson et al 2015).…”
Section: Dom Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…Field et al (1988) found that 30-50% of the soluble COD from bark water could be acidified into volatile fatty acids (VFAs) and between 7 and 36% could be converted by methanogenesis to methane after 8-9 days of anaerobic digestion. In the case that near complete removal of the remaining DOM was required, post-treatment by combined ozone and biological treatment may be effective at treating woodchip leachate (Zenaitis et al 2002;Svennson et al 2015).…”
Section: Dom Removalmentioning
confidence: 99%
“…Furthermore, ozonation has shown to be more effective than biological treatment alone for removing DOM from woodchip filter effluent. For example, in a laboratory study by Svennson et al (2015), 1.5 L of oak wood leachate was exposed to ozone at specific ozone doses between 0.7 and 7 g/L O 3 /g of initial COD removing .90% of polyphenols, up to 73% of COD, 61% of total organic carbon (TOC) and 97% of colour. A positive correlation between biodegradation and ozone pre-treatment was found.…”
Section: Introductionmentioning
confidence: 99%